Startups in the Shadows: Compliance, Licensing, and Capital Challenges for Fintech in KP - Gul, Shabana; Kalim, Zaryab (Dialogue Social Science Review (DSSR), 2025)
This study examines the regulatory barriers affecting fintech adoption in Khyber Pakhtunkhwa (KP), Pakistan, using a qualitative, Interpretivist approach. Semi-structured interviews with fintech founders and executives, along with officials from the State Bank of Pakistan (SBP) and the Securities and Exchange Commission of Pakistan (SECP), were triangulated with document analysis of regulatory texts and policy reports. The findings highlight systemic barriers, including prohibitive licensing thresholds, disproportionate compliance costs, regulatory ambiguity around emerging technologies, and weak institutional presence in KP. While regulations such as the Electronic Money Institution (EMI) framework were designed to ensure financial stability, their centralized and rigid application disproportionately disadvantages early-stage fintech in peripheral regions. Compliance burdens, particularly anti-money laundering (AML) and know-your-customer (KYC) mandates, were found to consume a large share of operational budgets, with no tiered or phased models available. Additionally, unclear regulatory positions on blockchain, cryptocurrency, and decentralized finance (DeFi) deter innovation, while limited regional engagement exacerbates KP’s marginalization within Pakistan’s fintech ecosystem. The discussion integrates institutional theory and regulatory scholarship to demonstrate a misalignment between regulatory intent and practice, leading to a two-tier fintech environment. The study concludes that proportionate, region-sensitive, and phased regulatory frameworks, combined with clearer guidance on emerging technologies, are essential for inclusive fintech growth. Future research should further explore comparative regulatory models and the role of regional ecosystems in driving financial inclusion.